Causes of Death in Long-Term Nasopharyngeal Carcinoma Survivors - Yang, Shi-Ping; Rao, Ming-Yue; Chen, Qing-Shuang; Zhou, Ping; Lian, Chen-Lu; Wu, San-Gang (Frontiers in Public Health, 2022)
Purpose: To assess the causes of death (COD) and long-term survival after nasopharyngeal carcinoma (NPC) diagnosis. Methods: Using linked data from the Surveillance, Epidemiology, and End Results program, NPC patients diagnosed from 1990 to 2010 and followed-up >5 years were identified. Chi-squared test, Kaplan–Meier method, and Cox proportional hazard model were used for analyses. Results: Among the 3036 long-term NPC survivors, 1432 survived for >5-10 years and 1604 survived for >10 years. The most common COD was primary NPC (36.9%), followed by other causes (28.7%), other cancers (15.3%), cardiac disease (12.9%), and non-malignant pulmonary disease (6.2%). With a median follow-up of 125 months, deaths from NPC decreased with increasing time from diagnosis, while death because of cardiac disease and other causes increased. In those aged <50 years, death due to NPC remained the main COD over time, while cardiopulmonary disease-related death was the leading COD in patients aged ≥50 years. In White patients, death due to NPC decreased and death due to cardiac disease increased over time. Death from NPC remained significant in Black and Asian patients even 15 years after the diagnosis of NPC, while death due to cardiac disease significantly increased after 9 years of diagnosis in Black patients. Multivariate analyses showed that the independent factors associated with inferior NPC-specific survival were older age, Asians, American Indian/Alaska Native, regional stage, distant stage, and diagnosis in the early years. Conclusions: The probability of death from primary NPC remains significant even 15 years after the NPC diagnosis. Our study advocates continued surveillance for NPC survivors beyond the traditional 5 years. Individualized follow-up strategies are required for NPC patients of different ages and races.